The German labor market: still adjusting badly? - Werner Eichhorst; Lutz C. Kaiser (Institute for the Study of Labor (IZA), 2006)
In the late nineties, Germany was often seen as a laggard with respect to labor market and welfare state reforms with institutional inertia being reflected in notoriously sluggish employment growth and rising unemployment. Recent years, however, saw a complex sequence of reforms with regard to labor market-related institutions such as labor market regulation, social benefits, active and activating labor market policies and attempts to reduce the burden of payroll taxes and
Keywords: J32; J68; 330; last but not least